Aerodynamic study of FIFA-approved footballs - Alam, F.; Chowdhury, H.; Mustary, I.; Loganathan, B. (Procedia Engineering, 2015)
The game of football is world's most viewed, played and loved sport. Due to increasing technological advancements and demand for performance, the ball manufacturers have been developing new designs progressively since its inception over 100 years ago. A traditional spherical football made of 32 leather panels stitched together in 1970s has become 14 synthetic curved panels thermally bonded without stitches in 2006 and more recently 8 panels thermally bonded in 2010, and again some new designed balls in 2013. Despite being most popular game in the world, no data is available on aerodynamic properties of recently FIFA approved Adidas Cafusa (thermally bonded 32 panels), Nike Maxim (stitched 32 panels), Umbro Neo 2 Pro (stitched 14 panels, and MitreUltimax (stitched 26 panels) footballs. Hence the primary objectives of this study are to evaluate aerodynamic performance of these recently introduced balls and compare their aerodynamic properties. The aerodynamic forces and moments are measured experimentally for a range of wind speeds in wind tunnel. A field trial using professional players has also been undertaken. The aerodynamic forces and their non-dimensional coefficients were determined and compared. The player's perception was also discussed.